SUBJEKTIVITAS BISRI MUSTHOFA MENAFSIRKAN AYAT-AYAT KEMATIAN DALAM TAFSIR AL-IBRIZ LIMA’RIFATI TAFSIRI AL-QUR’AN AL-‘AZIZ BI AL-LUGHAH AL-JAWIYYAH - Afifah, Farida Nur; Anshori, Muflikh Syaifuddin (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
KH. Bisri Musthofa (1915-1977 CE) was a prolific Islamic scholar known for his writings and active involvement in various organizations. Many scholars have conducted research on his Tafsir Al-Ibr?z due to its uniqueness. In this study, KH. Bisri provides his subjective interpretation of verses related to death, using a symbolic model by likening objects in his surroundings. The focus of this research is to delve into the meanings of death in Tafsir Al-Ibr?z, along with the methods of interpretation and its philosophical significance, making it relevant to human life.The method employed in this research is the maudh?’i method, with Tafsir Al-Ibr?z as the primary data source, complemented by secondary data gathered from various books, journals, Quranic dictionaries, Arabic and Javanese dictionaries, and relevant scholarly research. Data analysis is conducted using a historical-critical-philosophical approach presented in a descriptive-analytical manner. The research findings include six meanings of death according to KH. Bisri Musthofa in Al-Ibriz: death as the end of worldly life, physical death, death of the heart, death as a blessing, death as punishment, and symbolic death. These meanings are explained through three methods: translation based on the Quranic text, symbolic interpretation or analogy using surrounding objects, and references to interpretations by previous scholars. The subjective interpretation of death by Kiai Bisri Musthofa is relevant to human life, as it imparts meaning to existence, urging individuals to make the most of their lives and adapt to the changing times, encompassing aspects of the individual, religion, and society.